Implementation of Multi-Level Inclusive Learning Management in Indonesian Schools of Kinabalu City Malaysia - Mutaqin, Zaenal; Riyanto, Yatim; Sholeh, Muhamad; Khamidi, Amrozi; Amalia, Kaniati (Edukasi, 2024)
As an educational institution catering to children of Indonesian Migrant Workers (PMI) who are characterized by a rich tapestry of cultural, tribal, racial, and religious backgrounds, alongside a spectrum of socio-economic challenges and legal uncertainties regarding their presence in the host nation, Sekolah Indonesia Kota Kinabalu (SIKK), Malaysia, underscores the critical necessity for inclusive educational practices. This study examines the implementation of multi-tiered inclusive learning management across elementary, junior high, and senior high school levels, focusing particularly on students with special needs. The research aims to evaluate planning, execution, and support mechanisms in fostering equitable educational opportunities. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. Findings reveal that SIKK has successfully implemented inclusive practices at the elementary level, including differentiated curricula, ongoing teacher training, and additional learning resources. However, inclusive practices at the junior high and senior high school levels are less effective, largely due to resource limitations, particularly the lack of special education teachers, with only one currently available. Challenges include insufficient resources, inadequate technical support, and differing perceptions of inclusion among stakeholders. Despite these obstacles, SIKK demonstrates significant efforts in inclusive education, underscoring the need for comprehensive policies and sustained government support. This research offers a novel perspective on the management of inclusive education within a multicultural and resource-limited context, highlighting the significance of collaborative engagement among multiple stakeholders and the need for contextually informed strategies to ensure sustainable implementation within the framework of Indonesian schools abroad, which face markedly intricate challenges.